Translation of Literature as a Tool to Enrich Target Language Literature - Faisal Raheem, Amna; Shah, Sabreena; Memon, Nayab Asif (Technium Social Sciences Journal, 2022)
Translation of literature is the translation of literary art forms such as poetry, novels, dramas, short stories, films etc. The mainstream critiques of translation looked down upon the translation of literature. Translation of literature is often considered as artificial. However, on the bright side, translation of literature can be seen as a positive phenomenon. It is not just a mechanical task; rather it is a process of new creation. Translation of literature is a work of art. A skilled translator is a gem, who can add many new aspects to the translated literature. This article analyses the translation of Arabic poem and the translation of the story of Ali Baba and forty thieves to explain that the translation of literature is a tool to enrich target language literature.